2021
DOI: 10.1111/jpn.13534
|View full text |Cite
|
Sign up to set email alerts
|

Illicium verum and Eucommia ulmoides leaf extracts promote nutrient availability and antioxidant capacity in piglets by upregulating duodenal and jejunal Nrf2/TNF‐α

Abstract: The effect of Illicium verum extracts (IVE) or Eucommia ulmoides leaf extracts (ELE) on nutrient availability, duodenal and jejunal antioxidant ability of Duroc ×Landrace × Yorkshire (DLY) and Chinese native Licha-black (LCB) piglets was investigated. Ninetysix piglets (48 DLY and 48 LCB respectively) without significant difference in body weight (11.22 ± 0.32 kg) were used in a 2 × 4 factorial design. Animals were randomly allocated to four treatments, and each had four replicates with three DLY and three LCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Autophagy maintains the stability of the internal environment by eliminating toxic substances, damaged organelles, and misfolded proteins [ 40 , 41 ]. If autophagy is inhibited, normal cell function will be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy maintains the stability of the internal environment by eliminating toxic substances, damaged organelles, and misfolded proteins [ 40 , 41 ]. If autophagy is inhibited, normal cell function will be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 can not only regulate the body's REDOX level, but also regulate the expression of related immune factors in the jejunum, which may be due to Nrf2 alleviating the intestinal damage caused by weaning stress [37,38]. Among these immune factors, TNF-α, IL-1β, and IL-6 play prominent roles in inflammatory responses by stimulating cytokine release from intestinal immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, cold stress could cause an increase in T-AOC, SOD, and GSH-Px levels [ 65 ] and the reduction of MDA levels [ 66 ]. Previous studies reported that EUE improved the antioxidant capacity of weaned piglets [ 31 , 67 ]. Additionally, the dietary chlorogenic acid-enriched extract (CGAE) from Eucommia ulmoides supplementation improved oxidative status in pigs [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eucommia ulmoides is rich in chemical components, such as iridoids, flavonoids, phenylpropanoids, lignans, and so on [ 19 , 28 , 29 ]. Eucommia ulmoides has a variety of biological activities, including growth promotion [ 30 ], metabolic regulation [ 28 ], antioxidant abilities [ 31 ], immune enhancement [ 32 ], anti-inflammatory abilities [ 28 ], and other effects. Chlorogenic acid, flavonoid, and rutin in Eucommia ulmoides have an obvious effect of promoting growth [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%